2017
DOI: 10.5114/kitp.2017.72228
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of surgical embolectomy in patients with massive pulmonary embolism with and without cardiopulmonary resuscitation

Abstract: IntroductionPulmonary embolism is a challenging critical cardiovascular disease with high morbidity and mortality. Surgical embolectomy has favorable results in patients with massive pulmonary embolism.AimTo study the outcome of embolectomy in patients with massive pulmonary embolism.Material and methodsIn this single-center, retrospective study, 36 patients including 14 male and 22 female patients with a mean age of 50.80 ±18.89 years with acute pulmonary embolism who underwent surgical pulmonary embolectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Park [16] reported a 14.8% surgical treatment mortality rate. Reza [6] recently reported 36 massive PE surgical treatments with 10 deaths and a mortality rate of 27.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park [16] reported a 14.8% surgical treatment mortality rate. Reza [6] recently reported 36 massive PE surgical treatments with 10 deaths and a mortality rate of 27.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further research is needed to estimate the role of SPE in algorithmic PE treatment. Most studies were reported by authors from the USA, European countries, and from few developing countries [6]. The aim of this study is to assess the clinical outcomes of SPE for acute PE patients in a single cardiac centre in China.…”
Section: Introductionmentioning
confidence: 99%